PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP MINAT BELI KONSUMEN DI SITUS BELANJA ONLINE - Angriani, Rini; Purba, Tiurniari (SCIENTIA JOURNAL, 2022)
In 2021, there have been many online shopping sites that can be enjoyed by consumers in Indonesia. Several e-commerce sites began to compete with each other to attract consumers, so that every year e-commerce visitors always experience an increase and decrease. Based on Iprice Insight in Q4 2020, Shopee has the highest number of visitors compared to Tokopedia. In Q2 2021, Tokopedia visitors experienced an increase and Shopee dropped to the second position. This research is useful to identify the effect of service quality and trust on consumer buying interest through online shopping sites either simultaneous or partial. To obtain data, questionnaires will be distributed to 385 respondents. The data management analysis method in this study uses multiple linear regression hypothesis analysis using T and F tests using the SPSS version 25 application. The results of this study prove that simultaneously and partially service quality and trust have a positive and significant effect on consumer buying interest.